2019
DOI: 10.1515/rams-2019-0023
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of oil palm ash from boiler to nanoparticle

Abstract: This study aims to determine the characteristics of oil palm boiler ash (OPBA) after processing with ball mill and coprecipitation methods. The method used is OPBA from a palm oil mill, processed using a ball mill for 1 hour at a speed of 250 rpm. Then prepared with the coprecipitation method by dissolving it in 2M HCl solution and NaOH solution with variations (2; 2.5; 3) M. Particles were characterized by XRD, SEM, XRF, and FTIR. XRD characterization shows the size of each crystal (83,79; 72,30 and 56,31) nm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…In other words, Fourier transform infrared spectroscopy was used to investigate the chemical structure of the composites 49 . FTIR characterization of NR composites, shown in Figure 8, indicate the existence of several bond vibrations 50,51 : intense peaks between 2853 and 2962 cm −1 that could be attributed to CH stretching of the CH 3 group, at 1445 cm −1 (CH bending vibration) at 1375 cm −1 (scissoring vibration of the CH 3 group) and less intense peaks at 1663 cm −1 (C═C stretching) and at 838 cm −1 (plane bending vibration of CH bond in C═CH group). No differences were observed between FTIR spectra of composites with and without CPH fillers, probably because the CPH fillers were evenly spread on the rubber compound, confirming thereby the non‐covalent interaction between CPH and raw NR.…”
Section: Resultsmentioning
confidence: 99%
“…In other words, Fourier transform infrared spectroscopy was used to investigate the chemical structure of the composites 49 . FTIR characterization of NR composites, shown in Figure 8, indicate the existence of several bond vibrations 50,51 : intense peaks between 2853 and 2962 cm −1 that could be attributed to CH stretching of the CH 3 group, at 1445 cm −1 (CH bending vibration) at 1375 cm −1 (scissoring vibration of the CH 3 group) and less intense peaks at 1663 cm −1 (C═C stretching) and at 838 cm −1 (plane bending vibration of CH bond in C═CH group). No differences were observed between FTIR spectra of composites with and without CPH fillers, probably because the CPH fillers were evenly spread on the rubber compound, confirming thereby the non‐covalent interaction between CPH and raw NR.…”
Section: Resultsmentioning
confidence: 99%
“…The Scherrer equation (equation 2) is used to calculate the lattice strain and crystallite size. The peak width, β in radians, measured as full width half-maximum of an X-ray diffraction (XRD) spectra, is inversely proportional to the crystallite size L hkl perpendicular to the hkl plane [19,56]: Table 7 shows that lattice strain increases and crystallite sizes decrease with the increasing of machining parameters. The average crystallite sizes in the machiningaffected layer are smaller than bulk regions which is consistent with the microstructure observed in the backscattered electron images shown in Figure 5.…”
Section: Resultsmentioning
confidence: 99%
“…SEM of Bentonit-OPBA is presented in Figure 5. SEM analysis showed that structure is less aggregated this is probably caused by modifications with the use of CTAB surfactants on bentonite [17][18][19].…”
Section: Sem Analysismentioning
confidence: 98%